1997
DOI: 10.1176/ajp.154.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Visual information-processing impairments in deficit and nondeficit schizophrenia

Abstract: (2) and may represent a trait characteristic of the disorder (3). Attentional abnormalities have been found in unaffected relatives of persons with schizophrenia and in populations with subclinical dysfunctions thought to form part of the "schizophrenia spectrum" (3). Nevertheless, attention is not a unitary construct, and schizophrenia is most likely a heterogeneous disease; therefore it is unclear which aspects of attention are compromised in patients with schizophrenia and whether the impairment is related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…A replicated finding is that the RT benefit of trials with a valid cue relative to a neutral condition that does not provide information about where to attend tends to be larger in PSZ than in HCS (Gold et al, 1992; Liotti et al, 1993; Bustillo et al, 1997; Sapir et al, 2001). A recent study confirmed this phenomenon in a direct assessment using optimized task conditions (Spencer et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…A replicated finding is that the RT benefit of trials with a valid cue relative to a neutral condition that does not provide information about where to attend tends to be larger in PSZ than in HCS (Gold et al, 1992; Liotti et al, 1993; Bustillo et al, 1997; Sapir et al, 2001). A recent study confirmed this phenomenon in a direct assessment using optimized task conditions (Spencer et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Although many of these studies focused on examining possible lateralized abnormalities (Bustillo et al, 1997; Carter, Robertson, Chaderjian, Celaya, & Nordahl, 1992; Carter, Robertson, Chaderjian, O’Shora-Celaya, & Nordahl, 1994; Gold et al, 1992; Liotti, Dazzi, & Umilta, 1993; Maruff, Hay, Malone, & Currie, 1995; Posner, Early, Reiman, Pardo, & Dhawan, 1988; Sapir, Henik, Dobrusin, & Hochman, 2001; Strauss, Novakovic, Tien, Bylsma, & Pearlson, 1991; Wigal, Swanson, & Potkin, 1997), they also provide more general clues about visuospatial selective attention mechanisms in schizophrenia. Notably, collapsed across hemifields, the reaction time (RT) difference between trials with a valid cue (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, patients are able to use the advance information conveyed by spatial cues to allocate attentional resources to the expected target location prior to target onset. To ensure that reaction time differences between conditions reflect specific differences in functions of attentional selection rather than in general alerting effects of cues, several studies employed a neutral cue instead of a no-cue condition (e.g., Carter et al 1992, 1994, Bustillo et al 1997, Sapir et al 2001, Gouzoulis-Mayfrank et al 2004, 2007). These studies report essentially the same findings on cue usage.…”
Section: Attentionmentioning
confidence: 99%
“…The left graph presents averages across mean values reported by Bustillo et al (1997), Gold et al (1992), Oie et al (1998), Pardo et al (2000), Posner et al (1988), Wigal et al (1997), and Strauss et al (1991). These experiments include a total of 154 patients and 130 healthy controls.…”
Section: Figurementioning
confidence: 99%
“…If PSZ had an impaired ability to focus attention, then they should exhibit a smaller difference in performance between valid and invalid trials, but this validity effect is generally unimpaired in PSZ (Gold, Fuller, Robinson, McMahon, Braun, & Luck, 2006; Gold, Hahn, Strauss, & Waltz, 2009; Hahn et al, 2012). Moreover, a widely replicated finding is that the performance benefit of valid cues relative to spatially non-predictive cues is often greater in PSZ than in HCS (Bustillo, Thaker, Buchanan, Moran, Kirkpatrack, & Carpenter, 1997; Gold, Randolph, Coppola, Carpenter, Goldberg, & Weinberger, 1992; Hahn et al, 2012; Liotti, Dazzi, & Umilta, 1993; Sapir, Henik, Dobrusin, & Hochman, 2001; Spencer, Nestor, Valdman, Niznikiewicz, Shenton, & McCarley, 2011). This finding of enhanced cue validity suggests that PSZ hyperfocus on the cued location on valid trials or fail to distribute attention effectively on neutral trials.…”
mentioning
confidence: 96%